Prey stage preference and functional response of the seven-spot lady beetle Coccinella septempunctata to the rose aphid, Macrosiphum rosivorum. Issue 2 (1st February 2022) - Yang, Hui; Pu, De-Qiang; Wu, Bang-Yuan; He, Heng-Guo
ABSTRACT: The rose aphid, Macrosiphum rosivorum (Zhang), is a serious pest of roses in China. Currently, M. rosivorum is managed using almost exclusively with insecticides; therefore, effective, alternative strategies are needed to reduce this dependence on pesticides and the risk of the development of resistance in rose aphids. This study was conducted to evaluate the potential of the seven-spot ladybird, Coccinella septempunctata (L.), as a biological control agent of M. rosivorum in rose production fields. We determined the prey preference of C. septempunctata at constant densities of M. rosivorum for 1st – 4 th instar nymphs and for adults. The results showed that Coccinella septempunctata adults had its highest rate of consumption on 4 th instars and its lowest rate of consumption on adults among prey life stages. Furthermore, we defined the functional response of predator adults. C. septempunctata adults displayed a type II functional response on all prey stages. The highest attack rate and shortest handling time were for predators fed 1st instar aphids. The proportion of prey consumed by C. septempunctata was higher at lower densities for all stages of rose aphid, implying that C. septempunctata should be released early in an aphid infestation. Our study indicated that C. septempunctata has the potential to be used for control of rose aphids in rose-production fields.